1997
DOI: 10.1111/j.1744-6570.1997.tb00899.x
|View full text |Cite
|
Sign up to set email alerts
|

Video‐based Situational Testing

Abstract: In two separate studies, video‐based tests of situational judgment were developed and validated against measures of performance for hourly service workers. In the first study, 684 employees were used to develop a test of retail associate judgment and 787 newly hired employees were used to cross‐validate the instrument. In the second study, 412 current employees were used to develop a test of nursing home caregiver judgment and 148 newly hired caregivers were used to cross‐validate this video‐based test. In bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
140
2
9

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(156 citation statements)
references
References 17 publications
5
140
2
9
Order By: Relevance
“…In the meta-analysis of , it was found that SJTs show a correlation of 0.46 with cognitive ability, even though there was substantial variability around this estimate. For instance, video-based SJTs had lower correlations with cognitive ability than written SJTs (Weekley and Jones, 1997). Another example is that SJTs based on a job analysis were usually more highly related to cognitive ability than those not based on a job analysis (0.50 versus 0.38).…”
Section: Construct-related Validitymentioning
confidence: 99%
See 1 more Smart Citation
“…In the meta-analysis of , it was found that SJTs show a correlation of 0.46 with cognitive ability, even though there was substantial variability around this estimate. For instance, video-based SJTs had lower correlations with cognitive ability than written SJTs (Weekley and Jones, 1997). Another example is that SJTs based on a job analysis were usually more highly related to cognitive ability than those not based on a job analysis (0.50 versus 0.38).…”
Section: Construct-related Validitymentioning
confidence: 99%
“…Each scenario describes a person handling a typical job-related situation. At a critical "moment of truth", the scenario ends and the applicant is asked to choose among several courses of action (Dalessio, 1994;Smiderle et al, 1994;Weekley and Jones, 1997). Questions and response options are presented visually and supported by narration.…”
mentioning
confidence: 99%
“…Anastasi and Urbina define a situational test as`one that places the test taker in a situation closely resembling or simulating a``real-life'' criterion situation ' (1997, p. 450). Given this definition, examples of situational tests include accomplishment records (e.g., Hough 1984), situational judgement tests (e.g., Motowidlo, Dunnette and Carter 1990), situational interviews (e.g., Latham, Saari, Pursell and Champion 1980), video-based situational judgement tests (e.g., Weekley and Jones 1997), work samples (e.g., Robertson and Kandola 1982), and assessment centre exercises such as role-plays (e.g., Thornton 1992). Situational tests have also become known in the educational literature under the aliases of performance assessment, alternative assessment or authentic assessment (Baker, O'Neil and Linn 1993;Linn, Baker and Dunbar 1991;Messick 1994;Sackett 1998;Wiggins 1989).…”
Section: Situational Tests: Short Overview and Research Neededmentioning
confidence: 99%
“…O que parece ser uma concordância na literatura é que os TJS são importantes devido a sua capacidade pre ditora do comportamento humano para a situação exposta (Hanson & Ramos, 1996;McDaniel, Morgeson, Finnegan, Campion, & Braverman, 2001;Phillips, 1992Phillips, , 1993Weekley & Jones, 1997, 1999. Esse compor tamento, entretanto, pode ou não estar relacionado a processos de seleção, ao ambiente de trabalho e, além disso, pode ou não ser aquele que seria assumido pelo indivíduo avaliado, conforme já visto no que tange às instruções de respostas.…”
Section: Formatos Dos Testes De Julgamento Situacionalunclassified